Development of solar digital clock - Mohd Hafeez, Mohd Nasir (2009)
Solar energy is the light and radiant heat from the Sun that influence Earth’s climate and weather sustains life. Solar power is synonym to solar energy or more specifically to refer the electricity generated from solar radiation. Solar energy technologies can provide electrical generation by heat engine or photovoltaic means; space heating and cooling in active and passive solar buildings, day lighting, hot water, thermal energy for cooking, and high temperature process heat for industrial purposes. Since this technology is still new in Malaysia, so the using of solar as electric source is limited. So, in this case, I need to develop a system that uses solar power as basic supply to replace supply from Tenaga Nasional Berhad (TNB).The objectives of this project are to design a charger that uses solar as source to charge the battery. To supply the required voltage to the digital clock, a voltage regulator needed to stabilize the required output voltage from the battery to supply the microcontroller then digital clock. The first step to start this project is to make a thorough analysis about the panel solar that will be used for this project. After obtaining the data needed, a charger circuit must be design to charge the battery. This will ensure that the charger which will charge the battery are functioning and will be able to supply the digital clock circuits which have function as a load. Besides that, the digital clock needs to be design and use ATMEL 89S52 as controller. This digital clock will use 4 inch seven segment as the display instead of normal LED regarding to its advantages.